THE SWEAR WORDS ANALYSIS IN THE MOVIE ENTITLED THE WOLF OF WALL STREET - Leonardo Alexander Salim; Eko Budi Setiawan (Humaniora Scientia, 2020)
The research aims to discuss the kinds of swear words and thepurposes that consist in The Wolf of Wall Street. The objective of the research are todivide the swear words into groups based on their kinds and describe the purposes aswhy the swear words is used. The main theories that are used in this study are slangand swear words. The method of this research is descriptive research and thetechnique of data collecting used is library research. The result of the research are,there are many kinds of swear words that can be found based on Hughesclassification and the purposes as why people swearing is based on partridgeclassification. Based on Hughes classification there are seven kinds of swear words,swear words related to sex, swear words related to excrement, swear words relatedto name of animal, swear words related to personal background, swear words relatedto sexual activity, swear words related to taboo, religion, or oath, the last is swearwords related to mental illness. The result for the reasons as why people using swearwords are expressing anger, shock, disappointed, excitement, happiness, seriousness,confused, and proudness.